KEEFEKTIFAN TEKNIK SELF-INSTRUCTION UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMP - Fiorentika, Kasa; Santoso, Djoko Budi; Simon, Irene Maya (Jurnal Kajian Bimbingan dan Konseling, 2016)
The aim of this study was to determine the effectiveness of self -instruction techniques to increase the confidence of the students of SMPN 20 Malang . Data were collected using the inventory of confidence and analyzed with the Wilcoxon test through SPSS to students who have low self-esteem category . Results from the study are students who have a low level of confidence there are five people , students were given counseling group with the techniques of self -instruction , students are given a pretest - posttest to measure the effectiveness of a given technique , students increase confidence after attending group counseling techniques self- instruction.